Persuasion Strategies in Facebook Health Communication: A Comparative Study between Egypt and the United Kingdom - El-Dakhs Dina Abdel Salam; Ahmed Mervat M. (Open Cultural Studies)
The current study aims to examine the persuasive strategies used in Facebook posts by the Egyptian Ministry of Health and Population and the British Department of Health and Social Care. A total of 400 Facebook posts, 200 by each department of health, were analyzed for persuasion strategies using a recent persuasion model by Dontcheva-Navratilova et al. (2020). The findings showed that both departments primarily relied on ethos-based strategies, followed by logo-based strategies, while their use of pathos-based strategies was minimal. The findings also showed that the Egyptian posts included more direct appeals to the audience, logical reasoning, and emphasis on care and responsibility than the British posts. In contrast, the British posts employed the strategies of reference to expert opinion, creating a sense of community, reference to facts and statistics, and provision of exemplification and evidence significantly more frequently than the Egyptian posts. The results are interpreted in terms of the existing literature and relevant cultural models.